Optimalisasi Segmentasi Pasar Produk Juiceyo Di Kota Makassar - Pramita Ayu Lestari; St. Sabahannur; Andi Azrarul Amri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
The increasing public awareness of healthy lifestyles has not been fully supported by the availability of beverages that are truly pure without added sugar, water, or preservatives. This study aims to optimize market segmentation for JuiceYo products in Makassar City and to develop more effective marketing strategies. The research employed a descriptive approach, with data collected through a digital questionnaire distributed to 50 respondents. Data were analyzed based on demographic characteristics, consumer behavior, and purchasing power. The results indicate that the main market segment consists of Generation Z and millennials aged 20–29 years, accounting for 88% of respondents, dominated by students and employees with daily expenditures ranging from IDR 15,000 to IDR 30,000. A total of 96% of respondents considered the price of IDR 23,000 per bottle acceptable for a pure juice product. Digital marketing strategies through Instagram and WhatsApp proved effective in increasing market reach and consumer interest. These findings suggest that proper market segmentation can enhance marketing effectiveness and increase the sales potential of healthy fruit-based beverages.